Design of a curved surface constant force mechanism. Issue 2 (3rd April 2017) - Liu, Yang; Li, De-Jun; Yu, De-ping; Miao, Jian-guo; Yao, Jin
ABSTRACT: A new curved surface constant force mechanism which mainly consists of a roller and a curved surface has been proposed. The magnitude and the direction of normal force caused by squeezing between the roller and the curved surface satisfy a certain relationship, thus the decomposed force of the normal force keeps constant in a certain direction all the times. According to the envelope theorem, the trajectory of the roller center and the profile of the curved surface are obtained by ignoring friction. Then, the influence of the friction is discussed in detail. In addition, the simulation is performed to verify the theoretical calculation. The simulation results show that the output force is relatively constant and the friction has little effect on the output force.